Congenital Muscular Torticollis: A Descriptive Study of 16 Cases (Bangladesh Journal of Child Health, 2012)
Background and study aim: Torticollis is the postural deformity of head and neck. Congenital Muscular Torticollis (CMT) is a postural deformity of head and neck detected at birth or shortly after birth, primarily resulting from unilateral shortening of Sternocleidomastoid muscle (SCM). In neonates and infants, patient may be cured conservatively by physiotherapy but surgery is the treatment of choice for children and adolescents. There are various techniques of surgery. Division of both sternal and clavicular head of SCM is very easy method which was practiced in this study. Here we show our experience regarding conservative and surgical management of congenital muscular torticollis in neonates, infants and older children. Patients and Methods: This is a retrospective case study among sixteen patients of congenital muscular torticollis. The cases were enrolled consecutively between Nov 2005 to Oct 2008 in Bangabandhu Sheikh Mujib Medical University, Gonosasthaya Somaj Vittik Medical College Hospital, ZH Sikder Womens Medical College Hospital and different private clinics of Dhaka city of Bangladesh. Neonates and infants of were treated conservatively with physiotherapy by manual stretching and others (more than one year) were treated surgically by transection of both sternal and clavicular head of SCM under ganeral anesthesia. Operated patients were released on following post operative day with advice to start physiotherapy on same day. Acquired torticollis, ocular torticollis, neurogenic torticllis, osteogenic torticollis, congenital muscular torticollis with other diseases were excluded from the study. Parents were the informants. Purpose of the study was explained and verbal consent was taken. Written consent was taken before surgical intervention. Results: Patients age ranged from 5 days to 15 years of which eleven were female and five male. SCM was shortened in all cases (9 on right side and 7 on left side). Of 16 patients, 3 neonates, 8 infants and 5 were more than 1 year of age. There was no associated anomaly. Out of 11 neonates and infants 10 cured conservatively with physiotherapy and another one significantly improved. Six were treated surgically including one failed physiotherapy till the age of one year. Post operative period was uneventful and there was no complication. Results were evaluated clinically and on the comments of parents. Conclusion: Most of the patients of congenital muscular torticollis can be treated conservatively during infancy. Division of both sternal and clavicular head of SCM is easy and safe surgical technique for the treatment of CMT of older children and adolescents. DOI: http://dx.doi.org/10.3329/bjch.v34i3.10359 BJCH 2010; 34(3): 92-98